2013
DOI: 10.2478/raon-2013-0011
|View full text |Cite
|
Sign up to set email alerts
|

Does initial 45Gy of pelvic intensity-modulated radiotherapy reduce late complications in patients with locally advanced cervical cancer? A cohort control study using definitive chemoradiotherapy with high-dose rate brachytherapy

Abstract: BackgroundComparing initial 45 Gy of pelvic intensity-modulated radiation therapy (IMRT) and non-IMRT in terms of the late toxicities associated with advanced cervical cancer that has also been treated with definitive concurrent chemoradiotherapy and high-dose rate intracavitary brachytherapy (HDRICB).Patients and methods This retrospective study included 320 stage IB2-IIIB cervical cancer patients treated with CCRT (83 IMRT and 237 non-IMRT). The two groups had similar stage and HDRICB ratings. Following 45 G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 18 publications
(34 reference statements)
1
17
0
2
Order By: Relevance
“…Our meta-analysis revealed that the frequency of acute grade 2–4 GI and GU toxicities and of chronic grade 3 GU toxicity was significantly lower in the IMRT group than it was in the control group. One study [ 10 ] did not provide the grades of toxicity and thus was not included in this portion of our analysis. A preliminary study indicated that IMRT was associated with less chronic GI toxicity than c-RT was in patients with gynaecologic malignancies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis revealed that the frequency of acute grade 2–4 GI and GU toxicities and of chronic grade 3 GU toxicity was significantly lower in the IMRT group than it was in the control group. One study [ 10 ] did not provide the grades of toxicity and thus was not included in this portion of our analysis. A preliminary study indicated that IMRT was associated with less chronic GI toxicity than c-RT was in patients with gynaecologic malignancies [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously described 31 , the clinical target volume (CTV) included the gross disease, cervix, parametrium, uterus, superior half of the vagina, cardinal ligament, presacral region, and regional lymph nodes (common, internal, and external iliac). The planning target volume (PTV) was extended from the CTV to account for organ motion and setup uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy consisted of cisplatin administered weekly at a dose of 40 mg/m 2 intravenously, for a maximal dose of 60 mg. The detailed drug administration protocol has been described in our previous study 31 . Chemotherapy was withheld if we observed any hematological toxicity of more than or equal to grade 3.…”
Section: Methodsmentioning
confidence: 99%
“…For the treatment of gynecologic cancers, most reports have shown that IMRT reduces bladder, bowel, rectal, and bone marrow dose and is associated with favorable clinical outcomes such as lower rates of acute GI, GU, and hematologic toxicity after whole-pelvic radiation therapy. 16,17 In this study, we compared IMRT and c-RT treatment plans in patients with postoperative recurrent cervical cancer, with respect to both tumor dose conformality and critical normal tissue avoidance. Our results showed that IMRT produced an obvious improvement in the conformality relative to the c-RT techniques (0.680 T 0.067 vs 0.300 T 0.054).…”
Section: Discussionmentioning
confidence: 99%